O processo de desenvolvimento de um aplicativo móvel multiplataforma para apresentar músicas que cantam sobre locais da cidade de Fortaleza - Araújo, Andrew Noronha de (2021)
This technical report presents the development process of the mobile application “Fortaleza in Music” through a descriptive and applied methodology. The mobile application, which mainly aims to present the songs that portray symbols that make up the urban spaces of the city of Fortaleza, is part of the research project “Music and imaginaries about the city of Fortaleza” of the Image, Consumption and Urban Experiences Research Group of the Institute of Culture and Art of the Federal University of Ceará supported by the Institutional Program for Scientific Initiation Scholarships. This report includes requirements gathering and system modeling, creation of user interfaces prototypes, presentation of methods and technologies applied in coding the system, as well as implementation of the application in an apps distribution platform and description of the app evaluation planning, among other complementary aspects of the development process.